Factors Affecting the Choice of Bachelor of Science in Agriculture as a Course in DEBESMSCAT - Jacob Frederick P. Velza; Michael O. Ogaya; Roger Yatan Ibañez Jr. (Journal of Nonformal Education, 2023)
The choice of a study program is an important decision as it forms the foundation of an individual's career and professional development. This decision can influence a student's future in terms of academic success, self-understanding, and career goals. This study examined the factors that influenced the choice of BS in Agriculture as a course in the DEBESMSCAT-Cawayan Campus and the students' perceptions and level of acceptance regarding this course. A quantitative research design was adopted, and data were collected through a survey questionnaire distributed to BS Agriculture students. The findings indicated that personal aspirations and interests, peer influence, limited options, and practical considerations were significant factors influencing course selection. Factors such as economic status, dream course, and ease of employment held varying levels of influence on students' decision-making process. The study also revealed that students perceived BS in Agriculture as a course that brought satisfaction, offered hands-on experience in agriculture, and presented favorable job prospects. The study emphasized the importance of intrinsic motivations, practical involvement, and career prospects in course selection. Furthermore, students acknowledged the course's value in providing knowledge and recognized its demand in national and international employment markets. These findings provided insights for educational institutions and policymakers to design strategies and support systems that catered to students' preferences, enhanced informed decision-making, and promoted agricultural education. Further research was recommended to explore the specific reasons behind these factors and delve deeper into students' motivations in choosing BS in Agriculture as a course.